Some preliminary remarks concerning sociolinguistic variation within the „Vulgar” Latin vowel system: as evidenced by the inscriptional data - Papini, Alessandro (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
This paper aims to investigate whether a statistical analysis of linguistic data in inscriptions may serve for the study of sociolinguistic variation within the Latin Language. In particular, this study focuses on the quantitative vs. qualitative phonemic opposition within the vowel system of the so-called “Vulgar” Latin. In order to do so, we will study the relative frequency of the <ae>/<ē> and <ae>/<ĕ> graphemic oscillations in three different corpora of both synchronic and syntopic - but diaphasically and diastratically different - inscriptions from the city of Rome (cf. Mancini 2014). All the inscriptions considered in this sample date back from ca. 50 AD to ca. 250 AD (the last date referring to the “end” ofso-called Classical Latin according to Adamik 2015). Our results may point to the existence of a “disturbance” within the quantitative-based vowel system of Classical Latin, at least as far as some sub-standard varieties of the language are concerned.